2014
DOI: 10.1007/s11102-014-0602-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative somatostatin analogues versus direct transsphenoidal surgery for newly-diagnosed acromegaly patients: a systematic review and meta-analysis using the GRADE system

Abstract: Pre-SA increases the chance of biochemical control of acromegaly 3 months after TSS in patients harboring GH-secreting pituitary macroadenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 28 publications
3
18
0
Order By: Relevance
“…The results of our study should be compared with conclusions of other reports, especially of meta-analyses reported quite recently. According to the first of these, pre-operative SSA increases the chance of biochemical control of acromegaly 3 months after transsphenoidal surgery in patients harbouring GH-secreting macroadenomas [13]. Another such meta-analysis reported on the safety of pre-operative SSA in acromegaly, and the favourable impact of pre-operative SSA on surgical results was restricted to the short-term cure rate in macroadenomas and invasive macroadenomas [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our study should be compared with conclusions of other reports, especially of meta-analyses reported quite recently. According to the first of these, pre-operative SSA increases the chance of biochemical control of acromegaly 3 months after transsphenoidal surgery in patients harbouring GH-secreting macroadenomas [13]. Another such meta-analysis reported on the safety of pre-operative SSA in acromegaly, and the favourable impact of pre-operative SSA on surgical results was restricted to the short-term cure rate in macroadenomas and invasive macroadenomas [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies document the advantageous effects of pre-surgical SSA administration in acromegaly [7][8][9], but others do not support this attitude [10][11][12]. Recently performed meta-analyses deliver conflicting data [13][14][15][16]. Some guidelines advise [5] presurgical SSA application, whereas other do not [3,4].…”
Section: Methodsmentioning
confidence: 99%
“…Given these observations, the use of preoperative SRIF analogs to improve surgical outcomes has been debated. Although studies have shown that postoperative biochemical control is in fact improved by presurgical SRIF analog treatment ( Carlsen et al, 2008 ; Nunes et al, 2015 ), the overall evidence is dampened by the short follow-up duration and insufficient prospective evidence.…”
Section: Somatotropin-release Inhibitory Factor Analogs In Currentmentioning
confidence: 99%
“…Immediate results of surgery are significantly better in pretreated cases (Carlsen et al 2008, Shen et al 2010, but the long-term results are conflicting: some authors report no difference (Shen et al 2010) while others report a slightly higher cure rate in the pretreated group at 5 years follow-up (41% vs 27%) (Fougner et al 2014). In a recent meta-analysis, the chance of surgical remission (GH nadir after OGTT !1 mg/l and normal age-matched IGF1) was overall higher in pretreated patients (Nunes et al 2015). However, the extent and quality of the currently available evidence supporting the routine use of presurgical SSA are low, so it is not recommended as a routine approach (Katznelson et al 2014).…”
Section: Surgerymentioning
confidence: 99%